2017
DOI: 10.1148/radiol.2016151875
|View full text |Cite
|
Sign up to set email alerts
|

US-guided Microwave Ablation of Hyperplastic Parathyroid Glands: Safety and Efficacy in Patients with End-Stage Renal Disease—A Pilot Study

Abstract: Purpose To evaluate the safety and efficacy of microwave ablation (MWA) in patients with end-stage renal disease and secondary hyperparathyroidism. Materials and Methods The study protocol was approved by the human ethics review committee. Between March 1, 2014, and June 30, 2015, 51 patients (25 men, 26 women; mean age ± standard deviation, 53.1 years ± 12.9) were enrolled. All patients had at least one enlarged parathyroid gland and secondary symptomatic hyperparathyroidism, which was treated with ultrasonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 40 publications
1
65
0
1
Order By: Relevance
“…In previous study, Zhou et al demonstrated the feasibility and efficacy of microwave ablation of parathyroid glands and showed that serum PTH and calcium decreased significantly after MWA in patients with SHPT 41 . In current study, we used US-guided RFA to treat parathyroid hyperplasia in 56 patients with SHPT caused by CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In previous study, Zhou et al demonstrated the feasibility and efficacy of microwave ablation of parathyroid glands and showed that serum PTH and calcium decreased significantly after MWA in patients with SHPT 41 . In current study, we used US-guided RFA to treat parathyroid hyperplasia in 56 patients with SHPT caused by CKD.…”
Section: Discussionmentioning
confidence: 99%
“…MWA was performed under local anesthesia with 2% lidocaine (Synera, Salt Lake City, UT, USA) at the puncture site. The hydrodissection technique was performed for nerve protection . With US guidance, 40 to 60 mL normal saline (NS) was first injected into the area around the parathyroid nodule to offer heat insulation and nerve isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Parathyroidectomy (PTX) is necessary for SHPT patients who are refractory to medical therapy . Recently, due to minimal injury, an effective decrease in intact parathyroid hormone (iPTH) and good repeatability, ultrasound (US)‐guided percutaneous microwave ablation (MWA) has been gradually accepted in clinical practice …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results have been reported with the use of microwave ablation (MWA), a minimally invasive ablation technique, to treat incipient and recurrent SHPT nodules [25,26]. The aim of the present study was to determine the CONTACT Ming-An Yu yma301@163.com Interventional Ultrasound Center, China-Japan Friendship Hospital, 2 Yinghua Dong Road, Beijing 100029, China feasibility of MWA in terms of short-term efficacy and safety in chronic renal failure patients with ectopic SHPT.…”
Section: Introductionmentioning
confidence: 99%